2018
DOI: 10.1038/s41418-018-0242-0
|View full text |Cite|
|
Sign up to set email alerts
|

A DHX9-lncRNA-MDM2 interaction regulates cell invasion and angiogenesis of cervical cancer

Abstract: Cervical cancer (CC) is the third most common carcinoma and the fourth leading cause of cancer-associated mortality in women. Here, we report that MDM2-DHX9 interaction mediates CC motility and angiogenesis in a long noncoding RNAdependent fashion. A long noncoding RNA, named lnc-CCDST, is significantly downregulated in CC tissues, and binds to pro-oncogenic DHX9. DHX9 is upregulated in CC tissue, and promotes CC cell motility and angiogenesis. The lnc-CCDST and DHX9 interaction promotes DHX9 degradation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 51 publications
(55 reference statements)
0
93
0
Order By: Relevance
“…19 In cervical cancer, lncRNA CCDST enhances the interaction of MDM2 with oncogenic protein DHX9 and facilitates DHX9 degradation, and eventually leading to the inhibition of angiogenesis. 20 Additionally, lncRNAs modulate the expression of specific mRNAs through the ceRNA network, which is also a critical manner to regulate tumor angiogenesis. For example, Sun et al found that LINC00968 reduces angiogenesis by impeding miR-423-5p-mediated PROX1 inhibition in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…19 In cervical cancer, lncRNA CCDST enhances the interaction of MDM2 with oncogenic protein DHX9 and facilitates DHX9 degradation, and eventually leading to the inhibition of angiogenesis. 20 Additionally, lncRNAs modulate the expression of specific mRNAs through the ceRNA network, which is also a critical manner to regulate tumor angiogenesis. For example, Sun et al found that LINC00968 reduces angiogenesis by impeding miR-423-5p-mediated PROX1 inhibition in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the E3 ubiquitin ligase MDM2 can interact with DHX9 and mediate the degradation of DHX9 through the UPS pathway (Ding et al, 2018). Thus, we tested whether HBx could hinder the MDM2-mediated degradation of DHX9 through ubiquitination.…”
Section: Hbx Inhibits the Ubiquitination Of Dhx9 Proteinmentioning
confidence: 99%
“…Long noncoding RNA (lncRNAs) and circular RNAs (cir-cRNAs) are important factors in human cancer pathogenesis [15,20,21]. Both lncRNAs and circRNAs lack the ability to encode proteins and circRNAs are characterized by the covalent conjunction and lacking of the 3′ and 5′ end.…”
Section: Discussionmentioning
confidence: 99%